Análise sobre as causas que levam os adolescentes à prática de atos infracionais - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2016)
This study examined the causes that lead teenagers to practice offenders of illegal acts, the family and the school, socializing agencies, in the contribution of the moral and intellectual formation of these young ones, as well as the importance of religion for the formation of the young citizen. For the development of the research it was used as theoretical contribution the theory of the social representations. Thirty adolescents participated in the research that pay socio-educational penalties in CESEIN of the Macapá city. The data were collected through questionnaires, with subjective questions and half-structured with the social support of agents that act there. During the research it was detected that the socializing agencies has a great importance in the social recovery process of the teens that pay socio-educational penalties, however still hold a distance to the school and religion. Another observed aspect was that the most of the young people interviewed are repeat offenders of illegal acts.
Keywords: Agências socializadoras; Ato infracional; Adolescentes - Atos infracionais; Adolescentes - Medidas socioeducativas; CNPQ::CIENCIAS SOCIAIS APLICADAS